Surface Electric Properties and Their Role in the Bioactivity of Implant Materials: A Comprehensive Review - Valentina Vadimovna Chebodaeva (Crystals, 2025)
The surface electric charge of biomaterials plays a pivotal role in determining their bioactivity and biocompatibility, especially in orthopedic and dental applications. This review analyzes recent progress (2015–2024) in understanding how electric properties, particularly surface charge and zeta potential, modulate cellular adhesion, proliferation, and differentiation. Negatively charged surfaces (−20 to −30 mV) were consistently associated with enhanced osteoblast activity and calcium mineralization, while positively charged surfaces often induced pro-inflammatory responses. We explore theoretical models of the electric double layer (EDL), methods for quantifying surface charge, and strategies for modifying surface potential to enhance biological outcomes. A comparative analysis of materials—hydroxyapatite coatings, PCL scaffolds, titanium surfaces, and piezoceramics—is provided. Finally, we highlight knowledge gaps in mechanistic understanding and emphasize the need for standardized protocols in evaluating the electric properties of biomaterials.